Professional Competence and Pedagogical Challenges: A Systematic Study of Non-Degree Teachers in Indonesia - Yulianika (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study analyzes Indonesia’s policy of recruiting non-degree teachers in remote schools and its effects on professional competence and educational quality. It aims to assess whether addressing teacher shortages through such policies compromises instructional standards in underserved areas. Design/methods – A systematic literature review was conducted, synthesizing scholarly articles, policy documents, and empirical studies from 2010 to 2024. Database searches applied strict inclusion criteria focusing on teacher qualifications and student outcomes. Thematic analysis identified key patterns regarding pedagogical skills, curriculum implementation, and assessment practices among non-degree teachers. Findings – Non-degree teachers help alleviate staffing shortages but exhibit gaps in lesson planning, curriculum delivery, and assessment competencies. These deficiencies correlate with reduced student achievement and inconsistent educational quality, especially in remote areas. Resource limitations and minimal professional development further exacerbate these challenges. Research implications/limitations – The study's reliance on secondary data and its focus on Indonesia’s rural contexts limit broader applicability. Variability in methodologies among the sources also affects interpretation consistency. Future research should incorporate field studies to validate and expand upon these findings. Practical implications – This study recommends implementing competency-based recruitment, mandatory professional development, and digital training integration. Policymakers should incentivize certified teachers' placement in remote areas and align recruitment policies with international competency standards. Originality/value – This study systematically maps the professional challenges faced by non-degree teachers and provides evidence-based recommendations. It contributes valuable insights for policymakers aiming to ensure quality education while addressing staffing gaps in remote regions.